Role of Fluorine Addition in Oxygen Plasmas for the Disinfection of Respirator Fabrics - Kolowrotkiewicz, Julia; Ribeiro, Rafael [UNESP]; Izumi, Gabriel [UNESP]; Silva, Luiz Henrique da [UNESP]; Nascimento, Letícia do; Duarte, Iolanda; Cruz, Nilson [UNESP]; Passeti, Tânia; Rangel, Elidiane [UNESP] (Wiley, 2025)
This study investigated the potential of using low-pressure plasmas for the disinfection of N95 respirator fabrics, employing mixtures of oxygen and sulfur hexafluoride (SF₆). The proportion of SF₆ introduced into the plasma was varied from 0% to 100%, with the oxygen proportion correspondingly reduced. Plasma was ignited by applying a radiofrequency signal to the lower electrode and grounding the upper electrode. Treatments were conducted in both electrodes. The structural integrity of the fibers was preserved following plasma treatment. Complete fabric sterilization was achieved under various treatment conditions, with minimal alteration to their physicochemical properties and no cytotoxic effects. These results suggest that this approach may offer a promising new route for fabric disinfection.
Keywords: fiber integrity; plasma sterilization; respirators fabric; reuse; Saccharomyces cerevisiae; SF6/O2 plasma mixtures